2017
DOI: 10.1007/978-3-319-54090-0_7
|View full text |Cite
|
Sign up to set email alerts
|

F4/80 as a Major Macrophage Marker: The Case of the Peritoneum and Spleen

Abstract: Tissue macrophages are a heterogeneous cell population residing in all body tissues that contribute to the maintenance of homeostasis and trigger immune activation in response to injurious stimuli. This heterogeneity may be associated with tissue-specific functions; however, the presence of distinct macrophage populations within the same microenvironment indicates that macrophage heterogeneity may also be influenced outside of tissue specialization. The F4/80 molecule was established as a unique marker of muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 111 publications
2
72
0
3
Order By: Relevance
“…We recently described MDSCs as a significant source of IL-27 (12), and it is tempting to speculate that these cells are a significant source of rising levels during infection. F4/80 is expressed in monocytes, macrophages, and eosinophils (54,55). An unexpected finding was that the frequency of these cells was not increased in septic pups.…”
Section: Discussionmentioning
confidence: 95%
“…We recently described MDSCs as a significant source of IL-27 (12), and it is tempting to speculate that these cells are a significant source of rising levels during infection. F4/80 is expressed in monocytes, macrophages, and eosinophils (54,55). An unexpected finding was that the frequency of these cells was not increased in septic pups.…”
Section: Discussionmentioning
confidence: 95%
“…Since alveolar macrophage is the major source of pro-inflammatory chemokines upon phagocytosis of urban air particles [20], we then examined whether macrophage was activated by PM to secrete KC in bleomycin-induced pulmonary fibrosis. Immunofluorescence revealed the number of cells co-expression of KC and F4/80, a major marker of macrophages [21], on day 2-lung sections was significantly greater in the Bleo+PM group than in the control group ( Figure 4E). These data suggest that KC released by macrophage upon PM activation recruits neutrophils in bleomycin-induced pulmonary fibrosis.…”
Section: Kc In Balf Recruits Neutrophilsmentioning
confidence: 98%
“…These results indicated that EZH2 overexpression promoted the macrophage recruitment, cell migration, and invasion via upregulating the expression of CCL5 in lung cancer cells. The in vivo subcutaneous xenotransplanted tumor model further confirmed that EZH2 knockdown inhibited lung cancer metastasis and macrophage recruitment, indicated by downregulation of molecular macrophage marker, F4/80 [ 35]. Meanwhile, the protein secretion of CCL5 was also inhibited by EZH2.…”
Section: Discussionmentioning
confidence: 62%